Investigation of Models for Online Runaway Detection at the Esterification of Acetic Anhydride with Methanol - Carsten Schmidt; Jürgen Schmidt; Jens Denecke; Yongbo Xin (Chemical Engineering Transactions)
Models for the online detection of runaway reactions in chemical plants promise to increase the safe operation of chemical processes. However, a general industrial application has not been achieved for these models. In this publication, three models suitable for online detecting ongoing runaway reactions have been identified from the literature and tested with an RC1 reaction calorimeter for the esterification of acetic anhydride with methanol. In total 16 tests were performed for both, normal operation and runaway reaction, and the usability of the models with the generated data was evaluated.